2021
DOI: 10.1021/acsami.1c17472
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Osteoporosis Problem—Multifunctional Injectable Hybrid Materials for Controlling Local Bone Tissue Remodeling

Abstract: Novel multifunctional biomimetic injectable hybrid systems were synthesized. The physicochemical as well as biological in vitro and in vivo tests demonstrated that they are promising candidates for bone tissue regeneration. The hybrids are composed of a biopolymeric collagen/chitosan/hyaluronic acid matrix and amine group-functionalized silica particles decorated with apatite to which the alendronate molecules were coordinated. The components of these systems were integrated and stabilized by cross-linking wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…Additionally, the strength of bone in the tetra-PEG@PEG-ALN hydrogels was significantly higher and exhibited a greater value of bending pressure after 3 months after materials implementation. Gilarska et al 119 presented a novel hydrogel-based alendronate delivery system for the combined application of osteoporosis treatment and bone regeneration. The multifunctional, biomimetic injectable hybrids that contain ALN molecules coordinated with apatite decorated silica particles, which are immobilized in collagen/chitosan/hyaluronic acid matrix by genipin crosslinking were fabricated.…”
Section: Hybrid Materialsmentioning
confidence: 99%
“…Additionally, the strength of bone in the tetra-PEG@PEG-ALN hydrogels was significantly higher and exhibited a greater value of bending pressure after 3 months after materials implementation. Gilarska et al 119 presented a novel hydrogel-based alendronate delivery system for the combined application of osteoporosis treatment and bone regeneration. The multifunctional, biomimetic injectable hybrids that contain ALN molecules coordinated with apatite decorated silica particles, which are immobilized in collagen/chitosan/hyaluronic acid matrix by genipin crosslinking were fabricated.…”
Section: Hybrid Materialsmentioning
confidence: 99%
“…While nature-based hydrogels are unable to withstand the pressure at the site of the bone injury because of their poor mechanical properties, their synthetic counterparts generally exhibit poor biocompatibility, lack interactions with targeted cells, and tend to cause adverse reactions in the body (Zheng et al, 2021). Composite hydrogels that combine the advantages of natural and synthetic hydrogels have been proposed to overcome these individual drawbacks (Utech and Boccaccini, 2016;Gačanin et al, 2017;Kettenberger et al, 2017;Kim et al, 2018;Segredo-Morales et al, 2018;García-García et al, 2019;Ghavimi et al, 2019;Akbari et al, 2020;Bai et al, 2020;García-García et al, 2020;Gilarska et al, 2021;Yoon et al, 2021); some of these composite hydrogels with their respective characteristics are reported in Table 3. However, given the treatment required to treat osteoporosis, a prolonged drug release time was the main aim while designing the target composite hydrogel, as discussed below.…”
Section: Composite Hydrogelsmentioning
confidence: 99%
“…Targeting extracellular pathways, OPG-loaded composite hydrogels capable of controlling the release of OPG can inhibit the binding of RANKL and RANK; therefore, the osteoclastic activation is reduced, while promoting bone regrowth and osseointegration in osteoporotic defects (Wang X. et al, 2021). Alendronate, which is widely used to alleviate osteoporosis by inhibiting osteoclasts, is one of the most common drugs loaded on hydrogels (Posadowska et al, 2015;Nafee et al, 2018;Li et al, 2020;Gilarska et al, 2021;Jiang et al, 2022); such a complex Frontiers in Bioengineering and Biotechnology frontiersin.org would likely inhibit the rate-limiting step in the cholesterol biosynthesis pathway, essential for osteoclast function (Fisher et al, 1999). In addition, it was observed that the loading of zoledronate does not affect its action; in fact, the inhibition of the degradation of the mineralized hydrogel and the resorption of the peri-implant bone are effectively carried out by the loaded and unbound zoledronate (Kettenberger et al, 2017).…”
Section: Adjuvants Commonly Used To Inhibit Osteoclastsmentioning
confidence: 99%
“…In this way, Tan et al saw the great potential of the joint use of collagen and chitosan and studied their interconnection in hydrogels [30]. In addition, this combination was used by Deng et al to develop a hybrid collagen-chitosan hydrogel by chemical crosslinked to improve the properties of collagen hydrogel in cardiovascular tissue regeneration [31]; by McBane et al in islet transplantation [32]; and by Gilarska et al in bone tissue remodeling [33]. Nevertheless, all the combinations of collagen and chitosan hydrogels studied so far require a chemical crosslinking to generate the structure, which complicates its obtaining and can compromise their cytotoxicity and cell viability.…”
Section: Introductionmentioning
confidence: 99%